2019
DOI: 10.1101/mcs.a004200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characterization of individuals with predicted deleterious PHIP variants

Abstract: Heterozygous deleterious variants in PHIP have been associated with behavioral problems, intellectual disability/developmental delay, obesity/overweight, and dysmorphic features (BIDOD syndrome). We report an additional 10 individuals with pleckstrin homology domain-interacting protein ( PHIP )-predicted deleterious variants (four frameshift, three missense, two nonsense, and one splice site; six of which are confirmed de novo). The mutation spectrum is diverse, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 16 publications
4
29
1
Order By: Relevance
“…Human DCAF14 functions in mitogenesis ( Farhang-Fallah et al, 2002 ; Podcheko et al, 2007 ), replication origin initiation ( Zhang et al, 2016 ), and regulation of the spindle assembly checkpoint ( Jang et al, 2020 ). DCAF14 is also a prognostic biomarker for metastatic melanoma ( De Semir et al, 2012 ), and deleterious de novo mutations in DCAF14 are associated with developmental abnormalities ( Webster et al, 2016 ; Craddock et al, 2019 ). However, it is not known whether DCAF14 functions in conditions of perturbed replication.…”
Section: Introductionmentioning
confidence: 99%
“…Human DCAF14 functions in mitogenesis ( Farhang-Fallah et al, 2002 ; Podcheko et al, 2007 ), replication origin initiation ( Zhang et al, 2016 ), and regulation of the spindle assembly checkpoint ( Jang et al, 2020 ). DCAF14 is also a prognostic biomarker for metastatic melanoma ( De Semir et al, 2012 ), and deleterious de novo mutations in DCAF14 are associated with developmental abnormalities ( Webster et al, 2016 ; Craddock et al, 2019 ). However, it is not known whether DCAF14 functions in conditions of perturbed replication.…”
Section: Introductionmentioning
confidence: 99%
“…T A B L E 1 Clinical characteristics of reported patients with PHIP gene variants, our patient and a 5-year-old female with an identical PHIP gene variant (Webster et al, 2016;Jansen et al, 2018;Craddock et The shortest pathway identified based on experimentally derived evidence connecting PHIP and HEXB was via the SMARCA4 protein, indicating that PHIP binds directly to SMARCA4 (Morgan et al, 2017), which in turn is observed to regulate expression of HEXB mRNA (Hendricks et al, 2004). Hence, the PHIP protein potentially influences the HEXB gene and subsequent protein function.…”
Section: Resultsmentioning
confidence: 96%
“…Dysmorphic features (97%), reduced cognition (94%), and behavioral/psychiatric problems (86%) were the most common or cardinal features of those with PHIP gene variants. Other common features included ophthalmologic problems (72%), obesity/overweight (64%), and chronic fatigue (50%) (Craddock et al, 2019; Jansen et al, 2018). This gene, when disturbed, has led to a clinical condition coined the Chung – Jansen syndrome recognized by the authors reporting on the disturbed gene and characterized by dysmorphic features, cognitive dysfunction, aberrant behavior, and childhood onset of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six modules (modules 1, 2, 7, 8, 9, 10) were characterized by enrichment of genes in the embryonic regions, consistent with a role for neurodevelopmental processes mediating susceptibility to obesity ( 93 , 94 ). In fact, these modules contained genes known to participate in brain development, but not functionally characterized with regard to obesity, such as Hmgcr ( 95 ), Klf7 ( 96 ), and Lmo1 ( 97 , 98 ), as well as genes whose role in both development and obesity have been functionally characterized, such as Sim1 ( 78 87 ), Creb1 ( 99 , 100 ), Nrp2 ( 14 ), and Phip ( 22 , 23 , 101 , 102 ).…”
Section: Discussionmentioning
confidence: 99%